Why nutrient loading reductions alone cannot suppress Cladophora proliferation: insights from a coupled nearshore ecological model - Yasasi Fernando; Lisa Yu; Alexey Neumann; David Depew; Reza Valipour; George B. Arhonditsis (Ecological Modelling, 2026)

Probabilistic electricity demand forecasting for buildings using a variational mode decomposition-attentive quantile network - Chun-Hao Huang; Yu-Shin Hu; I-Yun Lisa Hsieh (Energy and Buildings, 2026)

Interpretable deep learning reveals spatiotemporal MRI features of brain aging that align with neurodegeneration - Nikhil N. Chaudhari; Owen M. Vega; Phoebe Imms; Jaron M. Kawamura; Nahian F. Chowdhury; Tamara Jafar; Andrei Irimia; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; et al. (GeroScience, 2026)
Cortical thinning and atrophy are hallmarks of brain aging that have been characterized using magnetic resonance imaging (MRI). Brain aging involves many neuroanatomic features whose effects on brain structure remain unexplored. To address this challenge, we trained interpretable deep neural networks (DNNs) to estimate brain age (BA) from T 1 -weighted ( T 1 w) MRI. By identifying MRI features unapparent to humans, DNNs can find aging-related structural alterations above and beyond cortical thickness and atrophy. Using a novel approach to DNN interpretability, we mapped brain aging progression in 25,539 cognitively normal UK Biobank adults aged 45–83 years. Cortical aging is found to involve anatomic features becoming prominent during the 50s within frontolateral, mesolimbic, cuneal, and occipitotemporal regions. From these foci, aging-related features propagate to adjacent areas at rates peaking in the 60s. Cortical thinning and atrophy do not trend closely with neurodegeneration, but important DNN-identifiable anatomic features have spatiotemporal dynamics that match those of amyloid or tau. Our results challenge the assumption that MRI cannot map anatomic features trending with neurodegeneration. Interpretable DNNs can empower MRI to quantify anatomic aging as a process of spatial feature expansion from focal regions into nearby structures in the sequence of neurodegenerative pathology. Traditional morphometrics explain only ∼1% of variance in DNN-identifiable features, which clarifies why the former are insensitive to anatomic changes involving neurodegeneration. Our results conceptualize brain aging in the context of spatial and temporal parallels between anatomic senescence and neuropathology. These findings may help to map cognitively normal adults’ neurodegenerative anatomy even without PET measurements. Graphical Abstract

Sex and APOE genotype specific brain regional vulnerability to Alzheimer's Disease - Qi Zeng; Minghui Wang; Erming Wang; Xianxiao Zhou; Peng Xu; Vahram Haroutunian; Dongming Cai; Bin Zhang; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; et al. (GeroScience, 2026)
Alzheimer’s disease (AD) disproportionately affects women and carriers of the apolipoprotein E ε4 allele (APOE4), yet little is known about how sex and APOE interact to influence white matter (WM) integrity during disease progression. We integrated diffusion MRI and matched blood transcriptomic data to investigate these interactions and their underlying biological mechanisms. WM microstructure was quantified using diffusion tensor imaging (DTI) and neurite orientation dispersion and density imaging (NODDI), and regional vulnerability was assessed with a composite vulnerability score (CVS) derived from associations between diffusion features and AD severity across clinical traits in each of the four sex-APOE groups (female or male, with or without APOE4). Brain parcellation with the Eve atlas revealed regions consistently affected across sex-APOE groups (e.g., parahippocampal and superior temporal gyri) and regions specific to individual groups (e.g., the cingulum in females with APOE4 and the middle frontal gyrus in males without APOE4). Gene co-expression network analysis of the matched blood expression data identified gene subnetworks linked to group-specific regional vulnerability, including a muscle tissue morphogenesis module regulated by NEURL1B and HIST1H2BN associated with middle frontal gyrus vulnerability. These findings demonstrate that sex and APOE genotype jointly shape region-specific WM vulnerability and its molecular signatures in AD. Understanding these interactions provides novel mechanistic insights and may inform precision approaches to drug development, biomarker discovery, and clinical trial design for AD.

A Machine Learning-Empowered Quantitative Structure–Activity Relationship Model for Predicting the Plasma Half-life of Drugs in Dogs - Xue Wu; Pei-Yu Wu; Wei-Chun Chou; Lisa A. Tell; Zhoumeng Lin (The AAPS Journal, 2025)

Predicting the progression of MCI and Alzheimer’s disease on structural brain integrity and other features with machine learning - Marthe Mieling; Mushfa Yousuf; Nico Bunzeck; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; Susan Landau; Monica Rivera-Mindt; Leslie M. Shaw; Edward B. Lee; et al. (GeroScience, 2025)
Machine learning (ML) on structural MRI data shows high potential for classifying Alzheimer’s disease (AD) progression, but the specific contribution of brain regions, demographics, and proteinopathy remains unclear. Using Alzheimer’s Disease Neuroimaging Initiative (ADNI) data, we applied an extreme gradient-boosting algorithm and SHAP (SHapley Additive exPlanations) values to classify cognitively normal (CN) older adults, those with mild cognitive impairment (MCI) and AD dementia patients. Features included structural MRI, CSF status, demographics, and genetic data. Analyses comprised one cross-sectional multi-class classification (CN vs. MCI vs. AD dementia, n = 568) and two longitudinal binary-class classifications (CN-to-MCI converters vs. CN stable, n = 92; MCI-to-AD converters vs. MCI stable, n = 378). All classifications achieved 70–77% accuracy and 61–83% precision. Key features were CSF status, hippocampal volume, entorhinal thickness, and amygdala volume, with a clear dissociation: hippocampal properties contributed to the conversion to MCI, while the entorhinal cortex characterized the conversion to AD dementia. The findings highlight explainable, trajectory-specific insights into AD progression.

Life history strategies determine response to SRT driven crash in anammox bioreactors - Christian A. White; Edmund H. Antell; Sarah L. Schwartz; Jennifer E. Lawrence; Ray Keren; Lijie Zhou; Ke Yu; Wei-Qin Zhuang; Lisa Alvarez-Cohen (Water Research, 2025)

Insights from the international workshop on “Adapting agriculture to climate change and air pollution” - Evgenios Agathokleous; Lisa Emberson; Jie Pei; Kazuhiko Kobayashi; James D. Blande; Jo Cook; Chao Fang; Zhiyu Han; Hui Ju; Oliver Knopf; Tao Li; Bing Liu; et al. (Environmental Science and Pollution Research, 2024)

Defining an ageing-related pathology, disease or syndrome: International Consensus Statement - Emma Short; Ian M. Adcock; Bilal Al-Sarireh; Ann Ager; Ramzi Ajjan; Naveed Akbar; Michael A. Akeroyd; Ghada Alsaleh; Ghada Al-Sharbatee; Kambiz Alavian; Winfried Amoaku; Julie Andersen; et al. (GeroScience, 2024)
Around the world, individuals are living longer, but an increased average lifespan does not always equate to an increased health span. With advancing age, the increased prevalence of ageing-related diseases can have a significant impact on health status, functional capacity and quality of life. It is therefore vital to develop comprehensive classification and staging systems for ageing-related pathologies, diseases and syndromes. This will allow societies to better identify, quantify, understand and meet the healthcare, workforce, well-being and socioeconomic needs of ageing populations, whilst supporting the development and utilisation of interventions to prevent or to slow, halt or reverse the progression of ageing-related pathologies. The foundation for developing such classification and staging systems is to define the scope of what constitutes an ageing-related pathology, disease or syndrome. To this end, a consensus meeting was hosted by the International Consortium to Classify Ageing-Related Pathologies (ICCARP), on February 19, 2024, in Cardiff, UK, and was attended by 150 recognised experts. Discussions and voting were centred on provisional criteria that had been distributed prior to the meeting. The participants debated and voted on these. Each criterion required a consensus agreement of ≥ 70% for approval. The accepted criteria for an ageing-related pathology, disease or syndrome were (1) develops and/or progresses with increasing chronological age; (2) should be associated with, or contribute to, functional decline or an increased susceptibility to functional decline and (3) evidenced by studies in humans. Criteria for an ageing-related pathology, disease or syndrome have been agreed by an international consortium of subject experts. These criteria will now be used by the ICCARP for the classification and ultimately staging of ageing-related pathologies, diseases and syndromes.

Structural properties of cottonii seaweed (Kappaphycus alvarezii) gels in the presence of coconut milk - Oni Yuliarti; Aan Dwi Sentana; Chen Yu Ong; Zakyyah Abdol Rahim Yassin; Lisa Ng; Wen Min Koh (Food Hydrocolloids, 2023)

Single-cell transcriptome analysis revealing the intratumoral heterogeneity of ccRCC and validation of MT2A in pathogenesis - Jie Wang; Zili Zuo; Zongze Yu; Zhigui Chen; Xiangdi Meng; Zhaosen Ma; Jiqiang Niu; Rui Guo; Lisa Jia Tran; Jing Zhang; Tianxiao Jiang; Fangdie Ye; et al. (Functional & Integrative Genomics, 2023)

Systematic evidence on migrating and extractable food contact chemicals: Most chemicals detected in food contact materials are not listed for use - Birgit Geueke; Ksenia J. Groh; Maricel V. Maffini; Olwenn V. Martin; Justin M. Boucher; Yu-Ting Chiang; Frank Gwosdz; Phoenix Jieh; Christopher D. Kassotis; Paulina Łańska; John Peterson Myers; Alex Odermatt; et al. (Critical Reviews in Food Science and Nutrition, 2023)

The Toxicology Investigators Consortium 2022 Annual Report - Alexandra M. Amaducci; Sharan L. Campleman; Shao Li; Dana L. Karshenas; Meghan B. Spyres; Lynn A. Farrugia; A. Min Kang; Rachel E. Culbreth; Paul M. Wax; Jeffrey Brent; Kim Aldy; Jennifer Acciani; et al. (Journal of Medical Toxicology, 2023)

Pkhd1cyli/cyli mice have altered renal Pkhd1 mRNA processing and hormonally sensitive liver disease - Chaozhe Yang; Naoe Harafuji; Ljubica Caldovic; Weiying Yu; Ravindra Boddu; Surajit Bhattacharya; Hayk Barseghyan; Heather Gordish-Dressman; Oded Foreman; Zsuzsa Bebok; Eva M. Eicher; Lisa M. Guay-Woodford (Journal of Molecular Medicine, 2023)
Autosomal-recessive polycystic kidney disease (ARPKD; MIM #263200) is a severe, hereditary, hepato-renal fibrocystic disorder that causes early childhood morbidity and mortality. Mutations in the polycystic kidney and hepatic disease 1 ( PKHD1 ) gene, which encodes the protein fibrocystin/polyductin complex (FPC), cause all typical forms of ARPKD. Several mouse lines carrying diverse, genetically engineered disruptions in the orthologous Pkhd1 gene have been generated, but none expresses the classic ARPKD renal phenotype. In the current study, we characterized a spontaneous mouse Pkhd1 mutation that is transmitted as a recessive trait and causes cysticliver ( cyli ), similar to the hepato-biliary disease in ARPKD, but which is exacerbated by age, sex, and parity. We mapped the mutation to Chromosome 1 and determined that an insertion/deletion mutation causes a frameshift within Pkhd1 exon 48, which is predicted to result in a premature termination codon (UGA). Pkhd1 cyli/cyli ( cyli ) mice exhibit a severe liver pathology but lack renal disease. Further analysis revealed that several alternatively spliced Pkhd1 mRNA, all containing exon 48, were expressed in cyli kidneys, but in lower abundance than in wild-type kidneys, suggesting that these transcripts escaped from nonsense-mediated decay (NMD). We identified an AAAAAT motif in exon 48 upstream of the cyli mutation which could enable ribosomal frameshifting, thus potentially allowing production of sufficient amounts of FPC for renoprotection. This mechanism, expressed in a species-specific fashion, may help explain the disparities in the renal phenotype observed between Pkhd1 mutant mice and patients with PKHD1 -related disease. Key messages The Pkhd1 cyli/cyli mouse expresses cystic liver disease, but no kidney phenotype. Pkhd1 mRNA expression is decreased in cyli liver and kidneys compared to wild-type. Ribosomal frameshifting may be responsible for Pkhd1 mRNA escape from NMD. Pkhd1 mRNA escape from NMD could contribute to the absent kidney phenotype.

Risk factors for endometrial cancer in Black women - Todd R. Sponholtz; Julie R. Palmer; Lynn Rosenberg; Chu Chen; Yu Chen; Megan A. Clarke; Tess Clendenen; Mengmeng Du; Lisa Johnson; Linda M. Liao; Kara A. Michels; Kelli O’Connell; et al. (Cancer Causes & Control, 2023)

Evaluating vehicle fleet electrification against net-zero targets in scooter-dominated road transport - Chia-Yu Tsai; Tsung-Heng Chang; I-Yun Lisa Hsieh (Transportation Research Part D: Transport and Environment, 2023)

Interpreting biomonitoring data: Introducing the international human biomonitoring (i-HBM) working group's health-based guidance value (HB2GV) dashboard - Shoji F. Nakayama; Annie St-Amand; Tyler Pollock; Petra Apel; Yu Ait Bamai; Dana Boyd Barr; Jos Bessems; Antonia M. Calafat; Argelia Castaño; Adrian Covaci; Radu Corneliu Duca; Sarah Faure; et al. (International Journal of Hygiene and Environmental Health, 2023)

Cooperative feeding and foraging lateralization by Eden's whales off southern China - Bingyao Chen; Caiwen Wu; Lisa T Ballance; Dagmar Fertl; Huiping Jiang; Ying Qiao; Zhuoxuan Du; Yu Zhang; Feng Yang; Guang Yang; Robert L. Pitman (Marine Mammal Science, 2023)
We investigated surface feeding behaviors of Eden's whales ( Balaenoptera edeni edeni ) in northern Beibu Gulf, southern China, between April 3, 2018, and April 26, 2021. During 122 days at sea, 1,065 individual feeding events were recorded, and eight feeding behaviors were identified: two nonlunging (tread‐water and/or trap‐feeding, 7.7%, and a novel behavior we call “pirouette feeding,” 15.3%) and six lunging (right lateral lunging, RLL, 10.9%; left lateral lunging, 0.2%; upright lunging, 6.3%, vertical lunging, 18.5%; inverted lunging, 0.3%; cooperative lateral lunging, COL, 40.9%). During COL, 2–8 whales swam clockwise around a fish school and simultaneously performed RLL on surfacing—the first cooperative feeding behavior recorded for a Balaenoptera whale. Five lateralized feeding behaviors (entailing either a left or right rotation on the long‐body axis) accounted for 65.8% of individual feeding events, with a strong right‐side bias (99.7%). Lateralized behavior is prevalent in many vertebrates, including several species of rorquals, and we suggest that the right‐biased foraging lateralization among rorquals specifically allows them to keep their right eye on their prey (i.e., a sensory versus motor lateralization), and that this shared asymmetry among conspecifics may have preadapted Eden's whale for cooperative foraging.

Correction to: Novel characteristics of soluble fibrin: hypercoagulability and acceleration of blood sedimentation rate mediated by its generation of erythrocyte‑linked fibers - Dennis K. Galanakis; Anna Protopopova; Kao Li; Yingjie Yu; Tahmeena Ahmed; Lisa Senzel; Ryan Heslin; Mohamed Gouda; Jaseung Koo; John Weisel; Marilyn Manco‑Johnson; Miriam Rafailovich (Cell and Tissue Research, 2022)

Global maps of soil temperature - Jonas J. Lembrechts; Johan van den Hoogen; Juha Aalto; Michael B. Ashcroft; Pieter De Frenne; Julia Kemppinen; Martin Kopecký; Miska Luoto; Ilya M. D. Maclean; Thomas W. Crowther; Joseph J. Bailey; Stef Haesen; et al. (Global Change Biology, 2022)
Research in global change ecology relies heavily on global climatic grids derived from estimates of air temperature in open areas at around 2 m above the ground. These climatic grids do not reflect conditions below vegetation canopies and near the ground surface, where critical ecosystem functions occur and most terrestrial species reside. Here, we provide global maps of soil temperature and bioclimatic variables at a 1‐km 2 resolution for 0–5 and 5–15 cm soil depth. These maps were created by calculating the difference (i.e. offset) between in situ soil temperature measurements, based on time series from over 1200 1‐km 2 pixels (summarized from 8519 unique temperature sensors) across all the world's major terrestrial biomes, and coarse‐grained air temperature estimates from ERA5‐Land (an atmospheric reanalysis by the European Centre for Medium‐Range Weather Forecasts). We show that mean annual soil temperature differs markedly from the corresponding gridded air temperature, by up to 10°C (mean = 3.0 ± 2.1°C), with substantial variation across biomes and seasons. Over the year, soils in cold and/or dry biomes are substantially warmer (+3.6 ± 2.3°C) than gridded air temperature, whereas soils in warm and humid environments are on average slightly cooler (−0.7 ± 2.3°C). The observed substantial and biome‐specific offsets emphasize that the projected impacts of climate and climate change on near‐surface biodiversity and ecosystem functioning are inaccurately assessed when air rather than soil temperature is used, especially in cold environments. The global soil‐related bioclimatic variables provided here are an important step forward for any application in ecology and related disciplines. Nevertheless, we highlight the need to fill remaining geographic gaps by collecting more in situ measurements of microclimate conditions to further enhance the spatiotemporal resolution of global soil temperature products for ecological applications.

Novel characteristics of soluble fibrin: hypercoagulability and acceleration of blood sedimentation rate mediated by its generation of erythrocyte-linked fibers - Dennis K. Galanakis; Anna Protopopova; Kao Li; Yingjie Yu; Tahmeena Ahmed; Lisa Senzel; Ryan Heslin; Mohamed Gouda; Jaseung Koo; John Weisel; Marilyn Manco-Johnson; Miriam Rafailovich (Cell and Tissue Research, 2022)
Soluble fibrin (SF) in blood consists of monomers lacking both fibrinopeptides A with a minor population in multimeric clusters. It is a substantial component of isolated fibrinogen (fg), which spontaneously self-assembles into protofibrils progressing to fibers at sub-physiologic temperatures, a process enhanced by adsorption to hydrophobic and some metal surfaces. Comparisons of SF-rich (FR) and SF-depleted (FD) fg isolates disclosed distinct molecular imprints of each via an adsorption/desorption procedure using gold surfaced silica microplates. Accelerated plasminogen activator-induced lysis and decreased stiffness (G′) of thrombin-induced FR fg clots were revealed by thomboelastography. Erythrocyte sedimentation (ESR) in afibrinogenemic plasma (Hematocrit 25–33%) was accelerated by FR fg nearly threefold that of FD fg. Stained smears disclosed frequent rouleaux formations and fibers linking stacked erythrocytes in contrast to no rouleaux by FD fg. Rouleaux formations were more pronounced at 4 °C than at ambient temperatures and at fiber-membrane contacts displayed irregular, knobby membrane contours. One of several FR fg isolates also displayed incomplete fiber networks in cell-free areas. What is more, pre-mixing FR fg with each of three monoclonal IgG anti-fg antibodies at 1.5 mol/mol fg, that inhibited fibrin polymerization, prevented rouleaux formation save occasional 2–4 erythrocyte aggregates. We conclude that spontaneously generated SF fibers bound to erythrocytes forming intercellular links culminating in rouleaux formation and ensuing ESR acceleration which in clinical settings reflects hypercoagulability. Also, the results can explain the reported fg binding to erythrocytes via ligands such as CD47, stable in vivo RBC aggregates in capillaries, and red areas of pathologic thrombi.

Hidden diversity of Macrophomina associated with broadacre and horticultural crops in Australia - Barsha Poudel; Roger G. Shivas; Dante L. Adorada; Martin J. Barbetti; Sean L. Bithell; Lisa A. Kelly; Natalie Moore; Adam H. Sparks; Yu Pei Tan; Geoff Thomas; Joop Van Leur; Niloofar Vaghefi (European Journal of Plant Pathology, 2021)

Novel Long-Acting Drug Combination Nanoparticles Composed of Gemcitabine and Paclitaxel Enhance Localization of Both Drugs in Metastatic Breast Cancer Nodules - Jesse Yu; Qingxin Mu; Simone Perazzolo; James I Griffin; Linxi Zhu; Lisa A McConnachie; Danny D Shen; Rodney JY Ho (Pharmaceutical Research, 2020)

The effects of lutein and zeaxanthin on resting state functional connectivity in older Caucasian adults: a randomized controlled trial - Cutter A. Lindbergh; Jinglei Lv; Yu Zhao; Catherine M. Mewborn; Antonio N. Puente; Douglas P. Terry; Lisa M. Renzi-Hammond; Billy R. Hammond; Tianming Liu; L. Stephen Miller (Brain Imaging and Behavior, 2020)

Adaptive capacity in social–ecological systems: a framework for addressing bark beetle disturbances in natural resource management - Stuart Cottrell; Katherine M. Mattor; Jesse L. Morris; Christopher J. Fettig; Pavlina McGrady; Dorothy Maguire; Patrick M. A. James; Jennifer Clear; Zach Wurtzebach; Yu Wei; Andrea Brunelle; Jessica Western; et al. (Sustainability Science, 2020)

Development and field assessment of transgenic hybrid switchgrass for improved biofuel traits - Lisa Alexander; Catherine Hatcher; Mitra Mazarei; Ellen Haynes; Holly Baxter; Keonhee Kim; Choo Hamilton; Robert Sykes; Geoffrey Turner; Mark Davis; Zeng-Yu Wang; Nicole Labbé; et al. (Euphytica, 2020)

Comparison of four modeling tools for the prediction of potential distribution for non-indigenous weeds in the United States - Roger Magarey; Leslie Newton; Seung Cheon Hong; Yu Takeuchi; David Christie; Catherine S. Jarnevich; Lisa Kohl; Martin Damus; Steven I. Higgins; Leah Millar; Karen Castro; Amanda West; et al. (Biological Invasions, 2018)

A novel Chromatiales bacterium is a potential sulfide oxidizer in multiple orders of marine sponges - Adi Lavy; Ray Keren; Ke Yu; Brian C. Thomas; Lisa Alvarez‐Cohen; Jillian F. Banfield; Micha Ilan (Environmental Microbiology, 2018)
Summary Sponges are benthic filter feeders that play pivotal roles in coupling benthic‐pelagic processes in the oceans that involve transformation of dissolved and particulate organic carbon and nitrogen into biomass. While the contribution of sponge holobionts to the nitrogen cycle has been recognized in past years, their importance in the sulfur cycle, both oceanic and physiological, has only recently gained attention. Sponges in general, and Theonella swinhoei in particular, harbour a multitude of associated microorganisms that could affect sulfur cycling within the holobiont. We reconstructed the genome of a Chromatiales (class Gammaproteobacteria) bacterium from a metagenomic sequence dataset of a T. swinhoei ‐associated microbial community. This relatively abundant bacterium has the metabolic capability to oxidize sulfide yet displays reduced metabolic potential suggestive of its lifestyle as an obligatory symbiont. This bacterium was detected in multiple sponge orders, according to similarities in key genes such as 16S rRNA and polyketide synthase genes. Due to its sulfide oxidation metabolism and occurrence in many members of the Porifera phylum, we suggest naming the newly described taxon Candidatus Porisulfidus .

Development and validation of KASP markers for the greenbug resistance gene Gb7 and the Hessian fly resistance gene H32 in wheat - Chor-Tee Tan; Hangjin Yu; Yan Yang; Xiangyang Xu; Mingshun Chen; Jackie C. Rudd; Qingwu Xue; Amir M. H. Ibrahim; Lisa Garza; Shichen Wang; Mark E. Sorrells; Shuyu Liu (Theoretical and Applied Genetics, 2017)

Multi-model ensemble projections of future extreme temperature change using a statistical downscaling method in south eastern Australia - Bin Wang; De Li Liu; Ian Macadam; Lisa V. Alexander; Gab Abramowitz; Qiang Yu (Climatic Change, 2016)

Hybridization of downregulated-COMT transgenic switchgrass lines with field-selected switchgrass for improved biomass traits - Holly L. Baxter; Lisa W. Alexander; Mitra Mazarei; Ellen Haynes; Geoffrey B. Turner; Robert W. Sykes; Stephen R. Decker; Mark F. Davis; Richard A. Dixon; Zeng-Yu Wang; C. Neal Stewart (Euphytica, 2016)

Attribution of extreme temperature changes during 1951–2010 - Yeon-Hee Kim; Seung-Ki Min; Xuebin Zhang; Francis Zwiers; Lisa V. Alexander; Markus G. Donat; Yu-Shiang Tung (Climate Dynamics, 2016)

Erratum to: A genome-wide association study of prostate cancer in West African men - Michael Blaise Cook; Zhaoming Wang; Edward D. Yeboah; Yao Tettey; Richard B. Biritwum; Andrew A. Adjei; Evelyn Tay; Ann Truelove; Shelley Niwa; Charles C. Chung; Annand P. Chokkalingam; Lisa W. Chu; et al. (Human Genetics, 2014)

A genome-wide association study of prostate cancer in West African men - Michael Blaise Cook; Zhaoming Wang; Edward D. Yeboah; Yao Tettey; Richard B. Biritwum; Andrew A. Adjei; Evelyn Tay; Ann Truelove; Shelley Niwa; Charles C. Chung; Annand P. Chokkalingam; Lisa W. Chu; et al. (Human Genetics, 2014)

A peroxiredoxin cDNA from Taiwanofungus camphorata: role of Cys31 in dimerization - Chih-Yu Huang; Yu-Ting Chen; Lisa Wen; Dey-Chyi Sheu; Chi-Tsai Lin (Molecular Biology Reports, 2014)

Learning Through Service: Student Perceptions on Volunteering at Interprofessional Hepatitis B Student-run Clinics - Leslie C. Sheu; Patricia Zheng; Anabelle D. Coelho; Lisa D. Lin; Patricia S. O’Sullivan; Bridget C. O’Brien; Albert Y. Yu; Cindy J. Lai (Journal of Cancer Education, 2011)

Compositional characterization and imaging of “wall-bound” acylesters of Populus trichocarpa reveal differential accumulation of acyl molecules in normal and reactive woods - Jin-Ying Gou; Simone Park; Xiao-Hong Yu; Lisa M. Miller; Chang-Jun Liu (Planta, 2008)

Bacterial diversity of metagenomic and PCR libraries from the Delaware River - Matthew T. Cottrell; Lisa A. Waidner; Liying Yu; David L. Kirchman (Environmental Microbiology, 2005)
Summary To determine whether metagenomic libraries sample adequately the dominant bacteria in aquatic environments, we examined the phylogenetic make‐up of a large insert metagenomic library constructed with bacterial DNA from the Delaware River, a polymerase chain reaction (PCR) library of 16S rRNA genes, and community structure determined by fluorescence in situ hybridization (FISH). The composition of the libraries and community structure determined by FISH differed for the major bacterial groups in the river, which included Actinobacteria , beta‐ proteobacteria and Cytophaga ‐like bacteria. Beta‐ proteobacteria were underrepresented in the metagenomic library compared with the PCR library and FISH, while Cytophaga ‐like bacteria were more abundant in the metagenomic library than in the PCR library and in the actual community according to FISH. The Delaware River libraries contained bacteria belonging to several widespread freshwater clusters, including clusters of Polynucleobacter necessarius , Rhodoferax sp. Bal47 and LD28 beta‐ proteobacteria , the ACK‐m1 and STA2‐30 clusters of Actinobacteria , and the PRD01a001B Cytophaga ‐like bacteria cluster. Coverage of bacteria with > 97% sequence identity was 65% and 50% for the metagenomic and PCR libraries respectively. Rarefaction analysis of replicate PCR libraries and of a library constructed with re‐conditioned amplicons indicated that heteroduplex formation did not substantially impact the composition of the PCR library. This study suggests that although it may miss some bacterial groups, the metagenomic approach can sample other groups (e.g. Cytophaga ‐like bacteria) that are potentially underrepresented by other culture‐independent approaches.

Biopharmaceutical Approaches for Developing and Assessing Oral Peptide Delivery Strategies and Systems: In Vitro Permeability and In Vivo Oral Absorption of Salmon Calcitonin - Patrick J. Sinko; Yong-Hee Lee; Vijaya Makhey; Glen D. Leesman; John P. Sutyak; Hongshi Yu; Barbara Perry; Curtis L. Smith; Peidi Hu; Erik J. Wagner; Lisa M. Falzone; Laura T. McWhorter; et al. (Pharmaceutical Research, 1999)

Abstracts of presentations on plant protection issues at the fifth international Mango Symposium Abstracts of presentations on plant protection issues at the Xth international congress of Virology - J. E. Peña; M. Wysoki; Gajendra Singh; Nancy Boscán de M.; Freddy J. Godoy; A. Obligado; C. J. Rossetto; I. J. A. Ribeiro; P. B. Gallo; N. B. Soares; J. C. Sabino; A. L. M. Martins; et al. (Phytoparasitica, 1997)

Macroscopic phototactic behavior of the purple photosynthetic bacterium Rhodospirillum centenum - Lisa Ragatz; Ze-Yu Jiang; Carl E. Bauer; Howard Gest (Archives of Microbiology, 1995)